Pengaruh Kualitas Kebersihan Pada Keputusan Pembelian Konsumen: Studi Kasus Kantin Universitas Islam Negeri Sumatera Utara - Imamsyah; Yudi Bimantaka; Siti Aisyah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The purpose of this study was to determine the effect of cleanliness quality on consumer purchasing decisions in the canteen environment of the State Islamic University of North Sumatra. In this study, the authors took a sample of students who often visited the canteen of the State Islamic University of North Sumatra within one week in order to obtain valid data. The research method used by the author in this study is a quantitative method, by collecting data from various aspects needed such as distributing questionnaires, interviews, and documentation. with the data that has been obtained from the respondents, the authors conclude that the students of the state Islamic university of North Sumatra prioritize the quality of cleanliness before deciding to purchase at the canteen of the state Islamic university of North Sumatra, which means that the variable cleanliness becomes a significant benchmark for the variable buying decision